The patterning of local variability during the acquisition of a novel whole-body continuous motor skill in young adults - Beerse, Matthew; Bigelow, Kimberly E.; Barrios, Joaquin A. (Experimental brain research, 2020)
There is increasing evidence that movement variability during motor skill acquisition plays a functional role. Specifically, initial variability might represent exploration of the possible motor space for solutions and error identification. Following practice, individuals might exploit a reduced amount of motor solutions to execute the task. While this variability pattern has been supported during discrete upper limb and multi-finger force tasks, there is a paucity of evidence for continuous whole-body motor tasks. Therefore, the purpose of this study was to characterize the role of variability during the acquisition of a whole-body continuous motor task across practice sessions in young adults. Twelve young adults aged 18–35-years participated in this study. Subjects practiced a novel, sagittal plane task, the kettlebell swing, using an online training video. We conducted an uncontrolled manifold analysis to partition local variability of the configuration of the kettlebell and body segments based on their impact on the position of the center-of-mass (COM) in the sagittal plane. Our results demonstrated that following initial practice, variability that did not affect the COM position remained elevated, suggesting sustained exploration of motor solutions. Following multiple practice sessions, variability related to motor solutions decreased, potentially indicating exploitation. The results from this study support the proposal that young adults initially utilize a range of motor solutions when acquiring a whole-body motor skill, followed by exploitation of stereotypic movement.